PERBANDINGAN HUKUM PENETAPAN UJRAH GADAI EMAS DI PEGADAIAN SYARI’AH DAN PERBANKAN SYARI’A - Reza Fahlevi Nurpaiz; Syarif Muhammad Yahya (Prodi Hukum Ekonomi Syariah (Muamalah), 2018)
Sharia gold Pawn is a form of financing on the basis of Sharia Sharia law without anyelement of RIBA. In Sharia gold pawnshop, the object is gold that has an exchange rateagainst a currency that tends to rise, which is very different from other pawn objects thattend to decline. A number of sharia financial institutions, including Bank Jabar Banten andPerum Pegadaian opened gold Pawn products in business transactions because in additionto the benefit is also relatively small risk. In fact, there are still few people who understandabout the sharia gold pawn product. This research uses a method of empirical approachthat is problem solving procedure by first researching existing secondary data thencontinued with research on primary data in the field. Data that is used is primary data thatis obtained directly from the field by using interviews, as well as secondary data obtainedby the Library study method. The analysis of the data used is a qualitative analysis of whichthe conclusion is deductive. Based on the results of the research, it can be knowncomparison of systematics determination in the product of Rahn Gold Mortgage applied byBank Jabar Banten Sharia and Perum Pegadaian Sharia Ciawi is on business developmentstrategy and why the product output is pawn.